2001
DOI: 10.1097/00005768-200111000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The aftereffects of dynamic exercise on ambulatory blood pressure

Abstract: The ABP difference after exercise is a function of initial values such that groups with the highest baseline BP experience the greatest postexercise ABP reductions. The ABP dynamic exercise studies raise important methodological considerations that should be attended to in future work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
1
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 33 publications
12
99
1
11
Order By: Relevance
“…[5][6][7] Higher levels of physical activity 8,9 and cardiorespiratory fitness 9 have been shown to reduce the risk of HPT in healthy normotensive persons. Acute 10,11 and chronic [12][13][14] exercise can also reduce resting blood pressure (BP) in hypertensive adults. Moreover, exercise training has been shown to improve several factors involved in the pathophysiology of HPT, including sympathetic activity, 15 endothelial function, 16 pulse wave velocity (PWV) 14 and insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Higher levels of physical activity 8,9 and cardiorespiratory fitness 9 have been shown to reduce the risk of HPT in healthy normotensive persons. Acute 10,11 and chronic [12][13][14] exercise can also reduce resting blood pressure (BP) in hypertensive adults. Moreover, exercise training has been shown to improve several factors involved in the pathophysiology of HPT, including sympathetic activity, 15 endothelial function, 16 pulse wave velocity (PWV) 14 and insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Data are available from a previous meta-analysis on both the acute and chronic effects of exercise on BP. 10 Baseline BP was also included as a predictor in this study and found to be a strong correlate of PEH magnitude. Nevertheless, mathematical coupling and regression to the mean would also be predicted to exert spurious influences in such analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers 10,11 have indicated that pre-exercise BP is a more important moderator of PEH than age, body mass index, waist circumference and maximal oxygen uptake. These findings have also been cited in the American College of Sports Medicine position stand on exercise and hypertension 12 to evidence the claim that the effectiveness of exercise in reducing BP would appear to be greatest in people with generally high BP status.…”
Section: Introductionmentioning
confidence: 96%
“…An additional inclusion criterion involved demonstrating (PEH), which was defined as at least a 3% reduction in mean arterial pressure (MAP) following acute exercise. 2 The protocol was split into three separate days. The first day consisted of medical screening, explanation of the protocol, and a peak oxygen uptake test ( .…”
Section: Methodsmentioning
confidence: 99%
“…1 The reduction in blood pressure (BP) following a single bout of exercise has been reported to persist for up to 11-12 h during ambulatory monitoring under freeliving conditions. 2 Postexercise hypotension (PEH) has therefore been implicated as a key mechanism in relation to the antihypertensive effects of exercise. 3 Although a well-established phenomenon, there is a wide variation in the magnitude of PEH response and differences in hemodynamic mechanisms between different populations.…”
Section: Introductionmentioning
confidence: 99%